Critical thinking an introduction to reasoning well - Watson, Jamie Carlin (Continuum, 2011)
An Introduction to Reasoning Well provides a concise and accessible introduction to logic and critical reasoning. Designed specifically to meet the needs of undergraduate students encountering philosophical logic and critical thinking for the first time, this comprehensive textbook covers all the themes and topics typically covered in an introductory course.